Teman Tani : Solusi Inklusif Layanan Asuransi Mikro Terintegrasi Sektor Pertanian Dalam Mencapai SDG 2030 - Azzahra, Belinda; Angga, I Gede (Agropross : National Conference Proceedings of Agriculture, 2022)
The agricultural sector is one of the main motors driving the wheels of a country's economy. The development and improvement of the sector is an integral part of the national development goals that have a significant and comprehensive impact. However, the risk of business uncertainty such as crop failure due to natural disasters and pest attacks also poses a threat to business continuity. Thus, the existence of financial instruments such as agricultural insurance is the right solution to minimize economic losses from these risks. Unfortunately, the existing agricultural insurance system is not yet effective enough to provide fast, easy, and inclusive services for farmers. Seeing these problems, the author proposes a policy recommendation, namely Teman Tani, as an improvement to the more integrated Rice Farmer Business Insurance (AUTP) system for the agricultural sector. Under this system, insurance companies will carry out branchless insurance through the OJK's Laku Pandai program which involves agents to expand insurance coverage to farmers. Then, the process of determining the amount of premiums and submitting claims will be made faster and on target through a decentralized data-exchange process that involves collaboration with the DataBott Company's Hara Application. In the process of payment and withdrawal of insurance funds, cooperation with banks and telecommunications companies will be carried out to make it easier for farmers through the mobile banking system. Therefore, the Teman Tani program can protect farmers from the risk of business uncertainty so as to increase productivity and achieve the goal of financial inclusion.